Adolescents’ Perceptions of Gender Discrimination in India: Do Perceptions Differ for Boys and Girls? - Chaudhary Nagaraj Nitasha; Vyas Amita; Landry Megan (Journal of Public Health International, 2019)
Despite the gains India has made in recent decades, it remains a country with vast gender inequities. Gender sensitization and empowerment programs aimed at young people, precisely at the time when they are forming their gender attitudes, has the potential to diminish gender inequity in the long-term. This study represents data from 36 qualitative in-depth interviews conducted amongst adolescent boys and girls enrolled in grade 7 in northern India, in schools that serve under-resourced communities. The interviews asked questions related to positive youth development, gender roles, violence, and locus of control. The results of the qualitative analysis provide insights into how adolescents perceive gender discrimination in their families and communnites. The majority of expectations for boys revolved around physical labor, while, for girls, gender roles were primarily focused on stopping education early to get married and take care of the household and children. Many of the responses from both boys and girls on privileges/restrictions were related to daughters not being fully educated while sons often were. Furthermore, when comparing between boys and girls (attributes) and understanding superiority, many participants noted there is a clear preference of boys compared to girls. Girls also had higher proportion of violence codes compared to boys, perhaps because many girls felt they were hit more frequently than boys. The results of this qualitative analysis provide direction for both future research as well as the development of gender sensitization interventions specifically designed for adolescents.
Keywords: Adolescent health